Managing Markets and Massification of Higher Education in India - Varghese, N. V. (International Higher Education, 2016)
The market friendly reforms of the 1990s encouraged proliferation of private higher education institutions and massification of the sector. Massification is accompanied by persisting inequalities, declining quality and poses challenges to effectively manage the system. This paper argues for a more regulated growth of private higher education and targeted public investments in favour of disadvantaged groups and deprived regions.